The impact of internet use on health investment behavior among middle-aged and elderly people: evidence from China - Yang, Xin; Bie, Mengjie; Zhang, Yuzheng; Li, Yundong (Frontiers in Psychology, 2025)
BackgroundWith the continuous deepening of global aging, improving the health level of the elderly has become one of the most critical issues. Health investment behavior is the key for middle-aged and elderly people (over 45 years old) to prevent future health risks. This study aims to explore the relationship between Internet use and health investment behavior among middle-aged and elderly people.MethodsA hypothesis model was constructed to explore the impact of internet usage on the health investment behavior of middle-aged and elderly people. The research was based on the data of 17,813 middle-aged and elderly people aged 45 and above from the 2018 China Health and Retirement Longitudinal Study. Quantitative analysis and fixed-effect models were employed to investigate the relationship between internet usage and the health investment behavior of middle-aged and elderly people.ResultsThe use of the Internet has a significant positive impact on the health investment behavior of middle-aged and elderly people, specifically manifested as a 4.2% increase in the probability of health investment and a 29.8% increase in the scale of health investment. This effect is statistically significant at the 1% level. The accumulation of health information capital plays a mediating role in the relationship between Internet use and the health investment behavior of middle-aged and elderly people, while educational attainment plays a moderating role in this process. In addition, the impact of Internet use on the health investment behavior of middle-aged and elderly people is heterogeneous, and this difference is mainly reflected in factors such as place of residence, income level, and age. Overall, Internet use has a more significant impact on the health investment behavior of urban residents, those with better economic conditions, and younger groups.ConclusionThe positive impact of Internet usage on the health investment behavior of middle-aged and elderly people is of great significance. The Internet can provide more opportunities for middle-aged and elderly people to obtain health information. The more they seek health information capital, the more obvious the effect of promoting health investment behavior will be.